Development of E-Comic–Based Instructional Media to Support Economics Learning at SMA Muhammadiyah Pangsid - Hasri Hasri; Erlita Erlita; Heril Heril; Harfiani Harfiani (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to develop e-comic–based instructional media and to examine its feasibility as a supporting medium for Economics learning at SMA Muhammadiyah Pangsid. The background of this research is based on the limitations of existing instructional media, which are still predominantly characterized by lecture-based methods and the use of textbooks, resulting in low student interest and engagement in the learning process. E-comic media was selected due to its advantages in integrating visual and narrative elements that can enhance students’ learning motivation and contextual understanding of economic concepts. This research employed a Research and Development (R&D) method by adapting the Borg and Gall model, which was simplified into seven stages: data collection, planning, initial product development, expert validation, product revision, limited field testing, and final product refinement. The research subjects consisted of tenth-grade students of SMA Muhammadiyah Pangsid. Data were collected through observation, interviews, and evaluation questionnaires administered to media experts, subject-matter experts, and students. The collected data were analyzed using quantitative and qualitative descriptive analysis techniques. The results indicate that the developed e-comic–based instructional media meets the criteria of being highly feasible for use in Economics learning. Evaluations from media experts and material experts showed very high levels of feasibility, while the results of student trials revealed positive responses regarding visual appearance, ease of use, and clarity of the presented material. The e-comic media was found to increase students’ learning interest and to assist them in understanding Economics material more effectively. Based on these findings, it can be concluded that e-comic–based instructional media is suitable for use as an alternative learning medium for Economics at SMA Muhammadiyah Pangsid and has strong potential to support more interactive, engaging, and meaningful learning experiences.